Slc6a13 Deficiency Attenuates Pasteurella multocida Infection-Induced Inflammation via Glycine-Inflammasome Signaling - Fang He; Yangyang Qiu; Xiaoyan Wu; Yaoyao Xia; Liu Yang; Chenlu Wu; Pan Li; Rui Zhang; Rendong Fang; Nengzhang Li; Yuanyi Peng (Karger Publishers, 2022)
We have previously demonstrated that Slc6a13-deficient (Slc6a13−/−; KO) mice are resistant to P. multocida infection, which might be in connection with macrophage-mediated inflammation; however, the specific metabolic mechanism is still enigmatic. Here we reproduce the less sensitive to P. multocida infection in overall survival assays as well as reduced bacterial loads, tissue lesions, and inflammation of lungs in KO mice. The transcriptome sequencing analysis of wild-type (WT) and KO mice shows a large number of differentially expressed genes that are enriched in amino acid metabolism by functional analysis. Of note, glycine levels are substantially increased in the lungs of KO mice with or without P. multocida infection in comparison to the WT controls. Interestingly, exogenous glycine supplementation alleviates P. multocida infection-induced inflammation. Mechanistically, glycine reduces the production of inflammatory cytokines in macrophages by blocking the activation of inflammasome (NALP1, NLRP3, NLRC4, AIM2, and Caspase-1). Together, Slc6a13 deficiency attenuates P. multocida infection through lessening the excessive inflammatory responses of macrophages involving glycine-inflammasome signaling.